Anesthesia management for patients with Prader-Willi syndrome undergoing bariatric surgery: a single-center retrospective case series study - Juan Tan; Haibei Liu; Huawu Yang; Dan Luo; Qiang Fu; Qiang Li (BMC Anesthesiology)
Abstract Background Prader-Willi syndrome (PWS) is a rare neurodevelopmental disorder resulting from abnormalities on chromosome 15q11.2-q13. These genetic anomalies pose significant challenges in anesthetic management when PWS patients undergo bariatric surgery. Methods We present five instances of anesthetic management in three PWS patients who underwent bariatric surgery under general anesthesia supplemented with nerve block techniques. Results Obesity, sleep apnea, airway ventilatory dysfunction, and hypotonia were the primary challenges faced by PWS patients in our study. We implemented specific strategies, primarily including the reverse Trendelenburg position, gradually deepening sedation, multimodal analgesia and perioperative progressive respiratory exercises. Only in case 1a, respiratory obstruction occurred during mask ventilation, which was resolved through the use of a nasopharyngeal ventilation tract. Additionally, delayed awakening was observed in case 1a postoperatively, with the spontaneous breathing showing minimal recovery following the administration of neostigmine and atropine. Extubation of the tracheal tube was performed on the first postoperative day. Upon her second admission (case 1b), we administered sugammadex as the neuromuscular blockade reversal agent, which facilitated successful tracheal extubation ten minutes post-procedure. Conclusions We advocate the use of sugammadex as the neuromuscular blockade reversal agent, the implementation of neuromuscular monitoring, progressive respiratory exercises, and multimodal analgesia in PWS patients undergoing bariatric surgery.